A 3D FIB‐SEM technique for quantitative characterization of oil shale's microstructure: A case study from the Shahejie Formation in Dongying Depression, China. Issue 1 (28th September 2020) - Zhao, Jianpeng; Dong, Xu; Zhang, Jinyan; Chen, Hui; Zhang, Wenjiao
Abstract: Investigating the pore structure of shale rocks plays an important role in understanding the mechanism of shale oil accumulation and migration; thus, it has a notable influence on the exploration and development of shale oil resources. In the present study, the microstructure of oil shale samples extracted from the Shahejie Formation in the Dongying Depression was investigated through the joint usage of focused ion beam (FIB) and scanning electron microscopy (SEM). Herein, we selected four representative samples. The SEM images of the sample surfaces milled by FIB indicated that pores were found in both the organic and inorganic matter. Organic pores were less developed in the samples because of the low thermal maturity of the organic matter. Continuous 3D digital rock images of shale samples were generated by FIB grinding and SEM in situ imaging. Based on multithreshold segmentation, the shale rocks were separated into different parts including kerogen, inorganic matter, and pores. The pore connectivity and pore size distributions were analyzed via Avizo software and in‐house developed MATLAB scripts. The pore size and corresponding volume distributions suggested that mesoscale pores (2‐50 nm) were abundant in the samples but they contributed limitedly to the total pore volume. Macropores (>50 nm) accounted for a small proportion but they had a greater contribution to the overall pore space volume. The coordination numbers of the subject four samples were mainly 0 and 1, which means that isolated pores accounted for the vast majority of the pores. These observations are critical to conduct reliable petrophysical simulations in the oil shales and understand their intrinsic properties accurately. Abstract : FIB‐SEM was used to identify the 3D structure of the oil shale with low maturity. Shale structures were characterized both in two and three dimensions. Mesoscale pores (2‐50 nm) were abundant in those oil shale samples, but they contributed less to the total pore volume.